"A Whitmanesque Song of the City": Colum McCann, 9/11, and New York Space. - Olster, Stacey (Contemporary Literature)
An excerpt from the article "Let the Great World Spin" by Colum McCann in the issue of "Contemporary Literature" is presented focusing on works of novelists between life below and life above ground level.